ANALYSIS OF THE HANNAFIN AND PECK INSTRUCTIONAL DESIGN MODEL ISLAMIC EDUCATION LEARNING - Nur Azizah, Rina; Nugraha, Mulyawan Safwandy; Dedih, Ujang; Diana, Aan (INTIHA: Islamic Education Journal, 2025)
In the context of Islamic Education, this model aims to create an interactive and responsive learning environment, emphasizing continuous evaluation to ensure the effectiveness and quality of the learning program. This study employed a qualitative approach with a descriptive qualitative method to gain an in-depth understanding of the model's application. Data collection methods include documentation and interviews. Data analysis follows the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing. Findings revealed that the Hannafin and Peck model effectively enhanced the learning process in Islamic education by providing a structured framework for needs analysis, design, development, and implementation. The model's continuous evaluation allows for ongoing improvements, making the educational experience more interactive and engaging for students. This study concludes that the Hannafin and Peck Instructional Design Model greatly benefits Islamic Religious Education at Raudhatul Athfal. The model ensures that educational programs have met students' needs and promote a deep understanding of Islamic teachings. However, challenges such as resource limitations and resistance to change must be addressed. Future research should focus on integrating technology and creating adaptive evaluation methods to enhance the model's effectiveness in various educational contexts.